A Research Agenda for the Massage Therapy Profession: a Report from the Massage Therapy Foundation - Sefton, PhD, LAT, ATC, JoEllen M.; Dexheimer, BSc, LMT, Jennifer; Munk, PhD, LMT, Niki; Miccio, MS, LMT, Robin; Kennedy, DrPH, LMT, Ann Blair; Cambron, PhD, LMT, Jerrilyn; MacDonald, BSc, Gordon; Hemsworth, BPE, RMT, Rob (International Journal of Therapeutic Massage & Bodywork, 2020)
The Massage Therapy Foundation (MTF) serves as a primary steward of massage therapy research; working to fund and advance the science and art of massage therapy for the entire massage community. The development of an updated research agenda is an essential part of furthering the MTF’s responsibility to help grow the massage therapy knowledge base and increase support for the application of quality research. Integrative health and massage community stakeholders are called upon to help move this MTF 2020 Massage Therapy Research Agenda forward. Together we must strive to continue to advance and disseminate new knowledge to all stakeholders including practitioners, students, instructors, researchers, and policy makers.